Improvements Glutation Levels in the Hippocampus of Aged and Oxidative-Stressed Rats by Supplementation of Alanine-Glutamine Dipeptide - Sunarno, Sunarno; Manalu, Wasmen; Kusumorini, Nastiti; Agungpriyono, Dewi Ratih (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2012)
Background: Physiological aging or aging due to oxidative stress causes to disruption of glutathione homeostasis of the hippocampus. Disruption of glutathione homeostasis characterized by a decrease in hippocampus glutathione levels below the normal threshold. Decreased levels of glutathione in the hippocampus was demonstrated decreased hippocampus function. One way to increase glutathione levels in the hippocampus and the function of hippocampus is to increase the concentrations of glutathione precursor. One of the glutathione precursors is alanine-glutamine dipeptide. This research was designed to obtain the most effective level of alanine-glutamine dipeptide supplementation to improve glutathione synthesis in the hippocampus of aged and oxidative-stressed rats. The highest glutathione concentrations in the hippocampus showed the best improvement on the hippocampus function in physiological aging or oxidative-stress aging rats.Design and Methods: The experimental rats were assigned into a completely randomized design with 2x2x4 factorial arrangement. The first factor was the age of the experimental rats, consisted of two levels i.e., 12 and 24 months. The second factor was oxidative stress consisted of two levels, i.e., without or with oxidative stress. The third factor was the level of alanine-glutamine dipeptide administration consisted of 4 concentrations, i.e. 0%, 3%, 5%, and 7%.Results: The results showed that administration of 7% alanine-glutamine dipeptide has resulted the highest levels of glutathione hippocampus in younger (0.0154 mg/mg tissue) or aged (0.0140 mg/mg tissue) rats or in normal (0.0150 mg/mg tissue) and in oxidative-stressed (0.0144 mg/mg tissue) rats. The increased hippocampus glutathione levels were associated to the improved functions of the hippocampus. Conclusion: alanine-glutamine dipeptide administration of 7% consentrations gave the best results on repair function of the hippocampus and has the potential to slow aging, both physiological aging or oxidative-stress aging rats (Sains Medika, 4(1):1-12).